The effect of cataloging anxiety on the job preference of library and information science students - Padoginog, Liezle E. (2008)
This study focused to determine whether the students of the School of Library and Information Studies taking cataloging subjects during the second semester of school year 2007-2008 are cataloging anxious and whether the students would consider cataloging for their future jobs. The study determined the predictors of work preference, namely: confidence, students' teacher perception, and subject usefulness. Among the respondents of this research were the students taking LIS 61 (Cataloging and Classification I) and LIS 62 (Cataloging and Classification II). The respondents were asked to catalog and answer a survey.